Third Year PPDM for Lake Limboto Coastal Communities Through Strengthening Marketing and Distribution Science and Technology Featured Product - Tineke Wolok; Weny Almoravid Dungga; Ismet Susila; Sartika Dewi Usman (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Iluta village is located on the shore of Lake Limboto which is often faced with flood problems during the rainy season and also serious problems of silting the Limboto lake as a result of the massive growth of water hyacinth. There are two main problems that need to be addressed in this program, namely: 1) efforts to reduce silting of Lake Limboto in a sustainable manner through the removal and use of water hyacinth as handicraft materials for hand-woven crafts by the local community, 2) community economic empowerment through strengthening the management capacity of various woven handicraft businesses. superior water hyacinth typical of Iluta village. The methods used include: 1) prioritizing problems to be addressed and divided into three years of activity, 2) reconstruction and improvement based on problems in stages every year, 3) improvements are carried out based on the approach of the local character of the local community. The results achieved are: 1) Management: implementing management functions gradually and continuously, 2) Human resources: applying management and business practices, 3) Finance: Managing finance, its resources and use gradually, 4) Production: arranging needs handicraft products as basic ingredients of water hyacinth and product standardization, 5) Marketing: Market survey and partnership with modern markets and online market expansion.